137Cs Dosimeter Irradiation Facilities: Calibration Frequency, Precision, and Accuracy. Issue 4 (April 2017) - Boria, Andrew J.; Rucinski, Blake D.; Abraham, Sara A.; Dawson, Alexander S.; Jawad, Ali H.; Miklos, Joseph A.; Kearfott, Kimberlee J.
Abstract : Abstract: Many dosimeter and instrument calibration sources, especially 137 Cs irradiators permanently installed in facilities, are infrequently calibrated since their geometry is not subject to large variation, their mechanisms are simple, and their operation can be visibly error-free for decades. Only decay corrections are needed to know delivered doses at fixed locations once a thorough characterization of such facilities is completed. For one such 137 Cs source, however, collected current values in a span of a few days were found to drop significantly. Malfunction of the internal positioning mechanisms through wear were found to be the cause. This paper suggests periodic source calibrations for the timely identification of source failures that could cause gross errors in dose delivery. In addition, a rigorous analysis of the magnitude of uncertainties and errors in dose delivery using a calibration source is included, which is based upon newly collected experimental data. This provides a technical basis for calibration procedures to ensure a given accuracy and precision of dose delivery.